2019
DOI: 10.1080/10810730.2019.1593554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Complementary Mass-Scale Media Interventions on Handwashing with Soap among Mothers

Abstract: Poor handwashing behavior is a major cause of morbidity and mortality globally. We evaluated two complementary mass-scale media interventions targeting mothers to increase the frequency of handwashing with soap; one using TV advertising, and the other mobile phone messaging. Television Commercials (TVCs): Mothers of 4-12 year-old children (n = 756) were randomly allocated among four arms: Three different branded TVCs and a fourth, control TVC unrelated to handwashing. TVCs were embedded in blocks of unrelated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…Our study revealed considerably high knowledge of COVID-19 symptoms, risk groups, and high levels of information from government sources. While mobile messages and TV commercials have been shown to be effective in promoting handwashing behavior in non-emergency settings (37), and messages leveraging prosocial (38) and deontological(39) motives may be effective in the context of COVID-19, our findings suggest the next steps for behavior change messaging campaigns should also focus on how to reach the most vulnerable (households in high poverty, comprised of older family members, household members with comorbidities, low education levels and low access to information or health services) and addressing concerns regarding loss of employment/income and food shortages to ensure that households are better able to comply with stay at home orders. Behavior change communication is critical and must be tailored to the living conditions of poor residents in urban slums, promote feasible behaviors, and use channels that will reach all sub-groups including those who are not literate or do not have a phone.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed considerably high knowledge of COVID-19 symptoms, risk groups, and high levels of information from government sources. While mobile messages and TV commercials have been shown to be effective in promoting handwashing behavior in non-emergency settings (37), and messages leveraging prosocial (38) and deontological(39) motives may be effective in the context of COVID-19, our findings suggest the next steps for behavior change messaging campaigns should also focus on how to reach the most vulnerable (households in high poverty, comprised of older family members, household members with comorbidities, low education levels and low access to information or health services) and addressing concerns regarding loss of employment/income and food shortages to ensure that households are better able to comply with stay at home orders. Behavior change communication is critical and must be tailored to the living conditions of poor residents in urban slums, promote feasible behaviors, and use channels that will reach all sub-groups including those who are not literate or do not have a phone.…”
Section: Discussionmentioning
confidence: 99%
“…CATIs) or HCF-based strategies for delivery of interventions, were rarely discussed. Limited attention was given to the importance of responding rapidly [44,113], particularly due to the hyper infective nature of newly shed V. cholerae from cholera cases [114] and lower infective dose required for transmission from cases in the first days of bacterial shedding [60], or repeated delivery of interventions [115,116], which are all important considerations for effective disease reduction.…”
Section: Effective Interventions To Reduce Within-household Transmissionmentioning
confidence: 99%
“…Eight socio-economic characteristics mentioned by previous studies influencing the HWT or other WASH behaviour were used: (1) water-related health problem [18,19], (2) information access [20,21], (3) mother and (4) father's education [19,[22][23][24][25] (5) wealth level [26,27], (6) religion [28][29][30], (7) accessibility [24,31], and (8) access to water [25]. An answer to the question "how often do you watch TV?"…”
Section: Socio-economic Characteristics (Secs)mentioning
confidence: 99%